Exploring university branding: employers’ expectation on university graduates on competency - Abdullah, Zulhamri (Student Management and Development Center (SISWA-UKM), 2018)
The study investigates the employers’ expectation on the competency among a leading Malaysian public university’s graduates. The expectation is based on the employer’s perception on our graduates’ capability and performance in their job. However, the incompetent university graduates have become a prevalent issue in the labor industry. Though the graduates have received higher learning education, they were perceived lacked in generic competencies that are vital in job performance. This has made the graduate employability becoming the national issue of the country. A quantitative survey approach employed in this study. The sampling frame was from university’s tracer study of consisting of employers’ data. The study used systematic random sampling to achieve theoretical generalization. The survey was administered by postal and online to encourage participation from the employers. The study assesses the competency of these graduates in seven skills which were communication, higher order thinking, leadership, technical, teamwork and personal traits. The outcome of the study revealed that the quality of our graduates in the labor industry is essential. Significantly, the graduates are indirectly carrying the university’s branding. Implementation of the study will improve the academic and curricular content in the university so that it will match with the industry’s demands.